Women's work : how culinary cultures shaped modern Spain - Ingram, Rebecca, 1977- (Vanderbilt University Press, 2022)
"A study of cooking as it relates to Spanish modernity and the roles of Spanish women"-- Provided by publisher.
Keywords: Food habits -- Spain.; Cooking -- Spain -- History.; Women -- Spain -- Social conditions -- History.; Social role -- Spain -- History.; Feminism -- Spain.; Spain -- Social life and customs.; Women -- Spain -- Social conditions.; Féminisme -- Espagne.; Rôle social -- Espagne -- Histoire.; Femmes -- Espagne -- Conditions sociales.; Habitudes alimentaires -- Espagne.; Espagne -- Mœurs et coutumes.; COOKING / History; Cooking; Feminism; Food habits; Manners and customs; Social role; Women -- Social conditions; Spain; Electronic books.; History; Literary criticism.; Critiques littéraires.